Diastasis of the symphysis pubis following normal vaginal delivery: Case report and review of the literature - Baykuş, Yakup; Kumbak Aygün, Banu; Deniz, Rulin; Kavak, Burçin; Çelik, Hüsnü; Gürateş, Bilgin (My University, 2010)
Separation of the pubic rami or diastasis of the symphysis pubis is an uncommon and usually asymptomatic complication in obstetrics. Acute, severe pain preventing mobilization might be seen in cases with separations more than ten milimeter. Conservative treatment with absolute bed rest, analgesics and pelvic bodice is successful in almost all patients and functional recovery is excellent at 6-8 weeks postpartum. In severe cases internal or external fixation might be required. We report a case with symphyseal separation presenting with acute hip and groin pain precluding ambulation in the postpartum period after an uneventful spontaneous vaginal delivery and review the literature. Copyright © 2010 by Türkiye Klinikleri.
Keywords: Pregnancy; Pregnancy complications; Pubic symphysis diastasis